The Evolution of the Study of Executive-Legislative Relations in Latin America: Or How Theory Slowly Catches Up with Reality - Carreras, Miguel (Revista Ibero-Americana de Estudos Legislativos, 2012)
The last twenty years have witnessed an explosion in the number of books and articles that focus on executive-legislative relations in Latin America. Since the publication of the seminal Linz article on the “perils of presidentialism” (1990), we have learnt a lot about the interaction between the executive and the legislative branch of government. This review article attempts to make sense of the evolution of the study of executive-legislative relations, by focusing on the inconsistencies between the mainstream theoretical approaches and the reality of executive-legislative relations in the region. Three major changes in the study of executive-legislative relations (unpacking of the “black box” of presidentialism, study of presidential coalitions, and analysis of impeachment processes) are discussed.